Fabrication and Characterization of Poly-Silicon Dioxide Nanogap Based on Capacitive Sensor by using Size Expansion Technique - Nazwa Taib (School of Nanoelectronic Engineering, 2012)
The aim of this research is to design, fabricate and characterize an array of planar nanogap capacitive sensor based on Poly-SiO2 structure by using size expansion technique.